(untitled) (Muitas Vozes, 2024)
In the linguistic turn of the 19th and 20th centuries, which questions the alleged neutrality of language, the outside was a strategy employed by certain thinkers, especially German and French ones, to escape the positivism of knowledge discourses. As a critical gesture towards modernity, this reflective position does not assert something, but unfolds discourses infinitely, even denying some of the most cherished elements of modern literature such as the authorship and the work of art. This permeates authors like Novalis, Friedrich Nietzsche, Martin Heidegger, Georges Bataille, Roland Barthes, Michel Foucault, and Maurice Blanchot. Focusing on the last one, especially his book "The Infinite Conversation" (1969), this paper discusses how the thought of the outside takes shape in two chronotopes, the 1800s and the 1970s, highlighting its influence on the respective understandings of literature. Finally, it reflects on its manifestation in contemporary Brazilian literature, in particular Hilda Hilst’s and Juliano Garcia Pessanha’s fiction.